Efektivitas Media KAKUTA (Kata KUnci Cerita) Terhadap Hasil Belajar Matematika Siswa Kelas III SDN 15 Mataram Tahun Ajaran 2023/2024 - Yusriah, Bajra Maya; Makki, Muhammad; Hidayati, Vivi Rachmatul; Fauzi, Asri (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2024)
The purpose of this study is to determine the effectiveness of KAKUTA (Story Keywords) media on mathematics learning outcomes of grade III students of SDN 15 Mataram for the 2023/2024 school year. The research method used is quantitative with the type of quasi-experimental research with research design used is nonequivalent control group design. The instruments used in this study were observation sheets on the implementation of the use of KAKUTA media and the story of addition and subtraction of the number of cacah. Based on the results of the data analysis carried out, the average pre-test score obtained from the experimental class was 64.78 and the control class was 74.76. And the average post-test score obtained from the experimental class was 83.04 and the control class was 77.14. The hypothesis is tested with the Independent Sample t-Test. From the test results that have been carried out, the results are 0.001 < 0.05. The N-Gain test results obtained are 66.29% with the category of quite effective, which means Ha is accepted and H0 is rejected. The conclusion of this study is that the KAKUTA (Story Keywords) media is effective for the mathematics learning outcomes of grade III students of SDN 15 Mataram for the 2023/2024 school year.